Dosier I: Agresividad, parafilia e inversión pericéntrica del cromosoma 9: Consideraciones a propósito de un caso - Sánchez Velasco, Miguel José (Quadernos de criminología, 2023)
In daily consultation you can find situations that invite you to delve into certain genetic and family aspects when signs and symptoms such as aggressiveness and hor- monal alterations concur. The realization of a family tree and a karyotype can shed light on these problems, allowing the design of different biopsychosocial approaches useful for doctors, lawyers or educators.